2017
DOI: 10.2147/pgpm.s145336
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian health care professionals’ knowledge, attitude, and interests toward pharmacogenomics

Abstract: BackgroundPharmacogenomics is a field of science which studies the impact of inheritance on individual variation in medication therapy response.AimWe assessed healthcare professionals’ knowledge, attitude, and interest toward pharmacogenomics.MethodsA cross-sectional survey was conducted using a 32-item questionnaire among physicians, nurses, and pharmacists who were working at the University of Gondar Referral and Teaching Hospital in northwest Ethiopia. Descriptive statistics was applied, and the categorical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…For instance, Elewa et al showed in 2015 a low mean awareness score among Qatari doctors and pharmacists about PG. 29 Furthermore, Abdela et al reported in 2017 a generally low knowledge about PG amongEthiopian healthcare providers 33. Similar results were additionally obtained from India37 and Kuwait 34.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…For instance, Elewa et al showed in 2015 a low mean awareness score among Qatari doctors and pharmacists about PG. 29 Furthermore, Abdela et al reported in 2017 a generally low knowledge about PG amongEthiopian healthcare providers 33. Similar results were additionally obtained from India37 and Kuwait 34.…”
mentioning
confidence: 74%
“…The questionnaire was adapted from several instruments used elsewhere considering the aim of the current study. [29][30][31][32][33][34] Face and content va-…”
Section: Study Questionnairementioning
confidence: 99%
“…Several studies evaluated the knowledge and attitude of pharmacists toward genomics and pharmacogenomics world-wide and our study is the first to do so in the UAE. Despite the geographical spaces, pharmacists shared similar attitudes and concerns toward pharmacogenomics [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In our sample, the knowledge of pharmacists who worked or studied outside the UAE did not differ from those who worked or studied in the UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Future advances in genomic medicine and PGX will require health professionals to be equipped with the knowledge and tools in order to fully apply and implement PGX in clinical practice as best as possible [ 9 , 10 , 11 , 12 ]. Despite the emphasis and evidence on the importance of genomic medicine and PGX in clinical practice, many healthcare professionals express a lack of confidence in the implementation of PGX in practice [ 7 , 13 ]. This is fairly attributed to lack of education, a widely highlighted barrier, which can lead to knowledge gaps and difficulty in interpreting and communicating PGX results [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emphasis and evidence on the importance of genomic medicine and PGX in clinical practice, many healthcare professionals express a lack of confidence in the implementation of PGX in practice [ 7 , 13 ]. This is fairly attributed to lack of education, a widely highlighted barrier, which can lead to knowledge gaps and difficulty in interpreting and communicating PGX results [ 13 ]. Medical and health science students represent future health professionals, and their perceptions are essential to increasing awareness on personalized medicine and PGX [ 1 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%